2022
DOI: 10.1038/s42003-022-04054-9
|View full text |Cite
|
Sign up to set email alerts
|

Direct experimental observation of blue-light-induced conformational change and intermolecular interactions of cryptochrome

Abstract: Cryptochromes are blue light receptors that mediate circadian rhythm and magnetic sensing in various organisms. A typical cryptochrome consists of a conserved photolyase homology region domain and a varying carboxyl-terminal extension across species. The structure of the flexible carboxyl-terminal extension and how carboxyl-terminal extension participates in cryptochrome’s signaling function remain mostly unknown. In this study, we uncover the potential missing link between carboxyl-terminal extension conforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…As previous ndings indicate CraCRY to take a larger conformation upon illumination, for example the radius of gyration (Rg) increases from 33.5 Å to 34.1 Å, one may expect this to be re ected in the mass spectra and IM heatmaps, as we observed it before for the PYP mutants, for which we performed proof of principle experiments for comparison (Figure S1-3). 13 Those show an increase in the average charge state as well as the CCS, which both re ect a transformation to a larger conformation. The contradictory behavior of CraCRY upon illumination, i.e.…”
Section: Discussionmentioning
confidence: 95%
“…As previous ndings indicate CraCRY to take a larger conformation upon illumination, for example the radius of gyration (Rg) increases from 33.5 Å to 34.1 Å, one may expect this to be re ected in the mass spectra and IM heatmaps, as we observed it before for the PYP mutants, for which we performed proof of principle experiments for comparison (Figure S1-3). 13 Those show an increase in the average charge state as well as the CCS, which both re ect a transformation to a larger conformation. The contradictory behavior of CraCRY upon illumination, i.e.…”
Section: Discussionmentioning
confidence: 95%
“…As previous findings indicate Cr aCRY to take a larger conformation upon illumination, for example the radius of gyration (Rg) increases from 33.5 to 34.1 Å, one may expect this to be reflected in the mass spectra and IM heatmaps, as we observed it before for the PYP mutants, for which we performed proof of principle experiments for comparison (Figure ). Those show an increase in the average charge state as well as the CCS, which both reflect a transformation to a larger conformation. The contradictory behavior of Cr aCRY upon illumination, i.e., compaction in the lit state vs decompaction, when comparing our MS-based approach and smFRET or SAXS, may be a result of the different environments for assessing the light-triggered conformations.…”
Section: Discussionmentioning
confidence: 99%
“…To decipher the structural interaction and the conformational transition upon illumination, structure determining methods are needed that are capable of handling the flexibility of the CTE, where high-resolution methods like NMR or cryo-EM are limited. So far, X-ray crystallography, HDX-MS, or smFRET have been employed to elucidate the conformational change of Cr aCRY upon blue-light irradiation, where some conformational change of the flexible CTE and/or helix α22 due to illumination has been observed. ,, Although HDX-MS can be employed to characterize structural changes in a time-resolved manner, it suffers the ability to analyze directly the kinetics of structural changes, especially in the second and subsecond time regime . Factors affecting the detachment of CTE and the respective time scales of these structural transitions have not yet been comprehensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some studies have suggested that Cr aCRY adopts the red-light-absorbing FADH · state as its resting state 26 , 36 , 37 . However, a recent study showed that the conversion of FAD ox into FADH · turned on the interaction between Cr aCRY and a partner protein, ROC15 (Rhythm of Chloroplast 15), to synchronize the circadian clock with light 38 . Considering these paradoxical results, the resting and signaling states of FAD required for Cr aCRY to perform CRY function remain unclear.…”
Section: Discussionmentioning
confidence: 99%